Corporate co-evolution : a political perspective - Rodrigues, Suzana B.; Child, John, 1940- (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2008)
Corporate Co-Evolution is a work of major scholarship that develops broad macro-economic principles of corporate strategy by examining and analyzing the history and growth of Telemig, a major Brazilian telecommunications company. Analyzes the different domains of the corporate environment - economic, social, cultural and political - that impact on the evolution of companies Traces the multi-level changes in a major Brazilian telecommunications company, uncovering the dynamics of change over the course of 30 years Develops a broader contextual and historical perspective that enriches our underst.
Perspectives on co-evolution -- The economic and political context of telecommunications in Brazil -- Scope and method -- Foundations 1953-1985 -- Politicization 1985-1993 -- Reconstruction and demise 1993-2000 -- Organizational culture -- Corporate identity -- Metaphors and reflective imaging -- The politics of learning at a time of restructuring -- A political interest theory of corporate co-evolution.
"Blackwell Publishing"--Cover
Includes bibliographical references and indexes.
Print version record.
English.
John Wiley and Sons
Keywords: Telemig (Firm) -- History; Telemig (Firm); Telephone companies -- Brazil -- Minas Gerais -- History; Telecommunication -- Brazil -- Minas Gerais -- History; z -- x; z -- x; TECHNOLOGY & ENGINEERING -- Telecommunications; Telecommunication; Telephone companies; Brazil -- Minas Gerais; History